IMPLEMENTASI METODE EXTREME PROGRAMMING PADA SISTEM PELAYANAN PENGADUAN MASYARAKAT BERBASIS ANDROID - Rokhim, Abdul; Alimin, Alimin (LPPM ITB Yadika Pasuruan, 2023)
Abstract : In this research, several stages in working on applications are useful to make it easier for the public to build public complaint system applications. From the stages in the software design process, namely using the Extreme Programming Method which is one option for developing software. However, the Extreme Programming method has its own stages, namely the planning, design, implementation and testing stages. These stages also include the handling stages in building a software aimed at designing an Android-based public complaint system application. And this application also has 3 actors, namely admin, village head, and community. This application system contains information about public complaints. The Android-based public complaint application aims to make it easier for the public to make complaints at any time and to make it easier for admins to check complaints located in Randusari Village.